Assessment of the mental foramen location in a sample of Saudi Al Hasa, population using cone-beam computed tomography technology: A retrospective study - M. Nazargi Mahabob; Sameer Alzouri Sukena; Abdul Rouf Mohammed Al Otaibi; Sanusi Mohammad Bello; A. Misba Fathima (Universidad de Concepción., 2021)
Background: It is essential that the dentist understand the positional variations of the mental foramen to perform different types of dental procedures. This study was conducted to identify the position of the mental foramen among the Saudi population of Al Hasa. Material and Methods: According to the selection criteria of 200 CBCT images, 101 images were selected. The selected images were categorized into five groups with respect to patient age. Each image was evaluated from both sides of the mandible and then recorded in six classes (position I-VI) according to the horizontal position and three classes in the vertical position. Results: In the Saudi Al Hasa population, Type 4 (at the level of 2nd premolar) was the most common location for mental foramen in the horizontal direction, on the right side (n= 41; 40.6%) and on the left side (n=44; 43.6%). Mental foramen was found in the vertical location, Type 3 (below the apex of 1st and 2nd premolars) was found in the right side (n= 54; 53.5%) and left side (n=56; 55.4%). The position of mental foramen is not constant and changes according to gender and ethnicity. This warrants dentists to evaluate patients individually. Conclusion: Even though the present study was done with a small sample of patients it provides a picture about approximate location of mental foramen among the target group of a population.